Impacts of vegetation restoration type on abundant and rare microflora inreclaimed soil of open-pit mining area - Jing MA; Ziyi HUA; Yanjun CHENG; Yanfeng ZHU; Yongjun YANG; Fu CHEN (Meitan kexue jishu, 2024)
Vegetation restoration is crucial for improving the ecological environment of mining areas, which could promote the development of reconstructed soil, thus regulating biogeochemical cycles, and exerting ecosystem functions. Therefore, it is essential and necessary to conduct in-depth research on the impact of vegetation restoration on soil microbial communities in open-pit mining areas. In this study, surface soil samples were collected from six typical reclamation plots, including bare land (CK), Medicago sativa (GL), Hippophae rhamnoides (BL), Pinus tabulaeformis (CF), Populus tomentosa (BF), and Populus tomentosa + Pinus tabulaeformis (MF), located in the eastern waste dump of Heidaigou mining area of Zhungeer Banner, Inner Mongolia. High throughput sequencing, co-occurrence networks, and correlation analysis were used to explore the influential mechanism of vegetation types on soil abundant, rare bacterial and fungal community structural composition and diversity. Results showed that ① there were significant differences in the effects of different vegetation restoration types on soil physicochemical properties and enzyme activity (P<0.05). The soil organic matter content, ammonium nitrogen content, and leucine aminopeptidase activity were significantly higher than those of CK. BL performed the advantage in accumulating soil organic matter, nitrate nitrogen, and available phosphorus, while the urease, leucine aminopeptidase, and alkaline phosphatase activities were significantly increased (P<0.05). ② The vegetation type has significantly affected the composition of soil abundant and rare microbial communities (P<0.05), with more abundant and rare bacterial species than fungi, whereas the variation of fungal abundance was more significant, especially the rare fungi. The Shannon index of abundant and rare bacteria, and rare fungal communities in different vegetation restoration plots was higher than that in CK, while their community structures presented the significant differences (P<0.05). ③ Different vegetation restoration types have increased the network topology parameters and complexity of abundant and rare bacteria and fungi. The amplitude test results of removing nodes to change natural connectivity indicated that BL could enhance the stability of soil abundant bacterial network, abundant and rare fungal networks, as well as their resistance to external interferences. ④ Soil URE, SOM, and ALP were the dominant factors for changes of soil microbial community structure. For the BL plot, the pH value, SOM, AP, β- Glucosidase, URE, and ALP have significantly affected the abundant and rare microbial communities (P<0.05). In a word, the BL restoration model performed a better effect on improving soil quality during the ecological reclamation process in mining areas. The research results can provide theoretical basis for the development and utilization of soil microbial resources for vegetation restoration in the damaged mining areas.